2014
DOI: 10.1109/tpwrd.2013.2291866
|View full text |Cite
|
Sign up to set email alerts
|

A Technique to Mitigate Zero-Sequence Harmonics in Power Distribution Systems

Abstract: This paper presents a technique to mitigate zero-sequence harmonics in power distribution systems. The method is based on the concept of passive zero-sequence harmonic filters. However, its basic configuration has been expanded to create a double-tuned filtering feature. This feature makes it possible to trap two harmonics with one filter and is especially attractive in solving harmonic-caused telephone interference problems. Furthermore, this paper has shown that common utility service transformers can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In [3], zero-sequence passive filters were designed to solve the telephone interference problem in an actual feeder. In this section, the proposed plug-in active filter scheme is utilized to address the same problem.…”
Section: Application Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In [3], zero-sequence passive filters were designed to solve the telephone interference problem in an actual feeder. In this section, the proposed plug-in active filter scheme is utilized to address the same problem.…”
Section: Application Examplementioning
confidence: 99%
“…Nowadays, the main power quality concerns are related to the harmonics produced by small, mass distributed harmonic sources such as personal computers, energy efficient lights and so on [1][2]. Example problems caused by such harmonics include telephone interference in new suburban areas [3], overloading of concentric neutral cables [4], and pipeline induction [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This filter has positive/negative sequence impedance so it affects the flow of NZS harmonics. The second type is the transformer based ZS [16] and the Yg/delta transformer based single tuned ZS filter [17] and double tuned ZS filter [18].…”
Section: ) Transformer Connectionmentioning
confidence: 99%
“…For this purpose, the equivalent loading index developed in [18] is used to check transformer overloading. The index converts the harmonic currents passing through the transformer into an equivalent 60Hz current that produces that same heating effect.…”
Section: B Component Loading Assessmentmentioning
confidence: 99%
“…However, the increasing use of residential electronic devices is causing a significant collective impact on distribution networks (Wang et al, 2016). In fact, some studies have demonstrated substantial CAICEDO, ROMERO, AND ZINI economic losses due to electrical losses (Duarte & Schaeffer, 2010;Santiago et al, 2013)energy losses and the economic consequences of the use of small appliances containing power electronics (PE, and interference with telephone signals due to zero sequence harmonics (Bagheri & Xu, 2014;Jewel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%